Expansions and contractions of repetitive DNA elements reveal contrasting evolutionary responses to the polyploid genome shock hypothesis in Brachypodium model grasses - Decena, María Ángeles; Sancho, Rubén; Inda, Luis A.; Pérez-Collazos, Ernesto; Catalán, Pilar (Frontiers in Plant Science, 2024)
Brachypodium grass species have been selected as model plants for functional genomics of grass crops, and to elucidate the origins of allopolyploidy and perenniality in monocots, due to their small genome sizes and feasibility of cultivation. However, genome sizes differ greatly between diploid or polyploid Brachypodium lineages. We have used genome skimming sequencing data to uncover the composition, abundance, and phylogenetic value of repetitive elements in 44 representatives of the major Brachypodium lineages and cytotypes. We also aimed to test the possible mechanisms and consequences of the "polyploid genome shock hypothesis" (PGSH) under three different evolutionary scenarios of variation in repeats and genome sizes of Brachypodium allopolyploids. Our data indicated that the proportion of the genome covered by the repeatome in the Brachypodium species showed a 3.3-fold difference between the highest content of B. mexicanum-4x (67.97%) and the lowest of B. stacei-2x (20.77%), and that changes in the sizes of their genomes were a consequence of gains or losses in their repeat elements. LTR-Retand and Tekay retrotransposons were the most frequent repeat elements in the Brachypodium genomes, while Ogre retrotransposons were found exclusively in B. mexicanum. The repeatome phylogenetic network showed a high topological congruence with plastome and nuclear rDNA and transcriptome trees, differentiating the ancestral outcore lineages from the recently evolved core-perennial lineages. The 5S rDNA graph topologies had a strong match with the ploidy levels and nature of the subgenomes of the Brachypodium polyploids. The core-perennial B. sylvaticum presents a large repeatome and characteristics of a potential post-polyploid diploidized origin. Our study evidenced that expansions and contractions in the repeatome were responsible for the three contrasting responses to the PGSH. The exacerbated genome expansion of the ancestral allotetraploid B. mexicanum was a consequence of chromosome-wide proliferation of TEs and not of WGD, the additive repeatome pattern of young allotetraploid B. hybridum of stabilized post-WGD genome evolution, and the genomecontraction of recent core-perennials polyploids (B. pinnatum, B. phoenicoides) of repeat losses through recombination of these highly hybridizing lineages. Our analyses have contributed to unraveling the evolution of the repeatome and the genome size variation in model Brachypodium grasses.